VD_FINDINFO Jug-inc / 2010 / 54 vom 26. Juli 2010 - VD Tribunal cantonal (2010)
SUSPENSION DE LA PROCÉDURE, LITISPENDANCE, CHOSE JUGÉE | 21 CL, 22 CL, 120 al. 2 CPC, 123 CPC, 144 al. 1 CPC, 146 CPC, 475 al. 2 CPC